PROBLEMS OF INDIAN PUBLIC LIBRARIES IN THE DIGITAL ERA - Hasanmiya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Present we are going to study about the problems facing Indian public libraries and the strategies that can be helpful for address the problems in the digital Era. A library is a place of collection of books; library is an ancient social institution with a long history parallel to human civilization. Books, readers, and librarians are the three main components of a library. Mahatma Jotirao Phule, the pioneer of women’s education, said that lack of education is the main reason behind the backwardness of the society. In the digital Era, knowledge is said to be power, man’s power increases with his knowledge. Therefore, man should convert every moment of his life to add knowledge and increase his strength. Since ancient times, such knowledge has been preserved in the form of books, books are considered very valuable. The best place to acquire knowledge is the library and information center; there are various types of knowledge tools for imparting knowledge to the general public. Education should reach every section of the society as the circle of knowledge widens every day. To make the society progressive, remove the ignorance in the society, increase the appetite for knowledge among the readers and overall development of the society, there is no alternative but public libraries.